Redox equilibria of iron oxides in aqueous-based magnetite dispersions:Effect of pH and redox potential - Pang, S.C.; Chin, Suk Fun; Anderson, Marc A. (Elsevier, 2007)
The effect of pH and redox potential on the redox equilibria of iron oxides in aqueous-based magnetite dispersions was investigated. The ionic activities of each dissolved iron species in equilibrium with magnetite nanoparticles were determined and contoured within the Eh–pH framework of a composite stability diagram. Both standard redox potentials and equilibrium constants for all major iron oxide redox equilibria in magnetite dispersions were found to differ from values reported for noncolloidal systems. The “triple point” position of redox equilibrium among Fe(II) ions, magnetite, and hematite shifted to a higher standard redox potential and an equilibrium constant which was several orders of magnitude higher. The predominant area of magnetite stability was enlarged to cover a wider range of both pH and redox potentials as compared to that of a noncolloidal magnetite system.